A case of multiple bone fractures due to the use of topical corticosteroid therapy for psoriasis. (June 2015) - Gönül, Müzeyyen; Gönül, Engin
Abstract A 45-year-old man who had psoriasis had applied topical clobetasol 17 propionate ointment on his whole body 2–3 times a week after the bath for 20 years. Physical examination showed abdominal distension, atrophy all over the skin, psoriatic plaques on the trunk, and extremities and multiple striae on the shoulders and legs. Morning plasma cortisol level and ACTH stimulation test confirmed the diagnosis of hypothalamic insufficiency. Bone mineral densitometry showed severe osteoporosis. Multiple bone fractures in the vertebrae and costa were detected on lumbar magnetic resonance imaging, the 99Tc MDP whole-body bone scan, and thoracoabdominal computerized tomography imaging. Topical corticosteroid therapies have possible local and/or systemic side effects such as atrophy, telangiectasia, hypertricosis, and suppression of pituitary-adrenal axis. We present an interesting case with multiple bone fractures caused by long-time topical corticosteroid use.